2010
DOI: 10.1186/1471-2105-11-435
|View full text |Cite
|
Sign up to set email alerts
|

CircuitsDB: a database of mixed microRNA/transcription factor feed-forward regulatory circuits in human and mouse

Abstract: BackgroundTranscription Factors (TFs) and microRNAs (miRNAs) are key players for gene expression regulation in higher eukaryotes. In the last years, a large amount of bioinformatic studies were devoted to the elucidation of transcriptional and post-transcriptional (mostly miRNA-mediated) regulatory interactions, but little is known about the interplay between them.DescriptionHere we describe a dynamic web-accessible database, , supporting a genome-wide transcriptional and post-transcriptional regulatory networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 54 publications
3
105
0
2
Order By: Relevance
“…Previous computational methods for the identification of miRNA targets have solely relied on sequence analysis of miRNA-mRNA target sites (Bartel 2009). More recently, a number of tools introduced the use of highthroughput expression analysis to improve predictions of miRNA targets (Huang et al 2007;Ulitsky et al 2010) and the identification of gene networks controlled by miRNAs (Friard et al 2011;Huang et al 2011;Jayaswal et al 2011;Le Bechec et al 2011;Liu et al 2011;Xu et al 2011). All of the above procedures are based on the comparison of paired data sets of miRNA and mRNA expression data generated from specific microarray platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous computational methods for the identification of miRNA targets have solely relied on sequence analysis of miRNA-mRNA target sites (Bartel 2009). More recently, a number of tools introduced the use of highthroughput expression analysis to improve predictions of miRNA targets (Huang et al 2007;Ulitsky et al 2010) and the identification of gene networks controlled by miRNAs (Friard et al 2011;Huang et al 2011;Jayaswal et al 2011;Le Bechec et al 2011;Liu et al 2011;Xu et al 2011). All of the above procedures are based on the comparison of paired data sets of miRNA and mRNA expression data generated from specific microarray platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Circuits involving miRNAs are unique in that they can elicit particular dynamics that may be difficult to achieve by substituting a transcriptional repressor (Osella et al, 2011); interestingly, miRNAs preferentially target TFs in plants (JonesRhoades et al, 2006), creating a variety of these TF-miRNA subcircuits. One of the most well-studied examples among such cases is the miRNA-mediated feed-forward loop (Tsang et al, 2007;Friard et al, 2010) (shown in Figure 5), which is capable of eliciting a controlled genetic pulse. In general, one framework for understanding a large complex genetic network composed of multiple types of genetic interactions is to view it as a composition of smaller subcircuits, each with an identifiable function.…”
Section: Network Motif Discovery: Distilling Large Complex Networkmentioning
confidence: 99%
“…MicroRNA related data was downloaded from Mirtarbase [19] and MiRBase [20]. For gene regulation data we relied on several sources: Transmir [21], Pazar [22], TRED (Transcriptional Regulatory Element Database) [23], CircuitsDB [24].…”
Section: A Data Sources and Biocomputational Platformmentioning
confidence: 99%